Anatomic feasibility of endovascular reconstruction in aortic arch aneurysms. (February 2015) - Sonesson, B; Landenhed, M; Dias, N; Kristmundsson, T; Ingemansson, R; Koul, B; Malina, M; Resch, T
The purpose was to estimate the proportion of current open aortic arch reconstructions that might be feasible for endovascular repair. From all elective repair made in Southern Sweden in one center between 2005 and 2012, 129 open and eight endovascular aortic arch repairs were identified. The anatomy of the ascending arch and descending aorta as well as the arch vessels was categorized from multiplanar and axial computed tomography scans. Of 129 open cases, only two (1.5%) were suitable for endovascular repair. Among 137 all arch open and endovascular arch reconstructions performed during the study period, only 10 (7%) were candidates for endovascular repair. The most common exclusion for endovascular repair was an excessively large ascending aortic diameter. In conclusion, only a small proportion of patients having an open arch repair are suitable for endovascular arch repair, a finding related to the large diameter of the ascending aorta.